Correction to: Assessing recent recurrence after hepatectomy for hepatitis B-related hepatocellular carcinoma by a predictive model based on sarcopenia - Hong Peng; Si-Yi Lei; Xin-Hua Luo (World Journal of Gastroenterology, 2025)
Correction to “Assessing recent recurrence after hepatectomy for hepatitis B-related hepatocellular carcinoma by a predictive model based on sarcopenia. World J Gastroenterol 2024; 30 (12): 1727-1738 [PMID: 38617742 DOI: 10.3748/wjg. v30.i12.1727]”. In this article, figure 1 needs to be corrected.